Sulle malattie genetiche e la loro rivelazione - Mancuso, Vito (Filosofia, 2017)
On a world scale in excess of 5 million children per year are born with a genetic disease. This article argues that in these births the interpretation of the overall meaning of life is hidden: genetic diseases reveal the deception of tradi- tional points of view (which can be traced back to four main ones: guilty pain, revelatory pain, pedagogical pain, senseless and hollow distress) and point to the evolutionary perspective as the only sustainable representation of what is usually called the meaning of life. These definitively release from metaphysics and the corresponding theism according to which “everything has a sense”, and together, if carefully considered, save from nihilism and despair leading to the “nothing makes sense” approach, to state on the other hand that the meaning is dramatically con- structed in the development of the world itself.